PROGRAM HIPOTETIK BIMBINGAN DAN KONSELING PRIBADI UNTUK MENINGKATKAN STABILITAS EMOSI PADA PESERTA DIDIK: Studi Deskriptif terhadap Peserta Didik Kelas XI SMA Angkasa Lanud Husein Sastranegara Bandung Tahun Ajaran 2012/2013 - Pertiwi, Ratih (2013)
Adolescent period is a stage in which an individu arrives in an important period; transitional period, periode of changes, period of determining identity, the stage of age that evokes anxiety, unrealistic period, and as the threshold of adulthood. According to Gesel et al, it can be said that children at the age of 14 do not have stable emotion ao that their emotion easily fluctuates or changes. At the age of 16, children tend to have more stable emotion so that it causes they are able to control their emotion better. In Indonesa, the phenomenon is that children at the age of 16 still have unstable emotion and they are difficult to control their feeling. The general aim of the study is to formulate a hypothetical personal guidance and counseling program in the attempt to develop students' emotional stability of XI grade of SMA Angkasa Lanud Husein Sastranegara Bandung academic year 2012/2013. Moreover, the specific aim that the study want to achive is to acquire profile of students' emotional stability of XI grade of SMA Angkasa Lanud Husein Sastranegara Bandung academic year 2012/2013. The study uses descriptive reseach method to describe emotional stability of XI grade students of SMA Angkasa Lanud Husein Sastranegara Bandung academic year 2012/2013 and to formulate a hypothetical personal guidance and counseling program in the attempt to develop students' emotional stability. The population of the study is XI grade students of SMA Angkasa Lanud Husein Sastranegara Bandung Tahun Ajaran 2012/2013, the study uses random sampling technique in determining the sample of the study. This study employs non-test technique as the data collection technique using questionaire that reveals students' emotional stability. The results of the study show: (1) in general, level of students' emotional ability is in high category in all aspects except problem solving ability which is in average category. (2) the proper formula of hypothetical social guidance and counseling program approved by the experts and practitioners comprise: rational, vision ad mision formulation, operational base, description of needs, purpose of the program, component of the program, participants involved, operational planning, thematic development, service development, time allocation, the facilities, and evaluation. Recommendation of the study suggest guidance counselor teachers can use personal guidance and counseling program to develop emotional stability of XI grade students academic year 2013/2013. The program is formulated by the the researcher as the guideline of implementation service of personal guidance and counseling in the attempt to develop students' emotional stability. the study also recommends next researchers are able to compare general description of emotional stability of adolescent at the beginning period and adolescent at the final period so that it can be gained extended and comprehensive description and understanding. Keywords: A hypothetical personal guidance and counseling program, emotional stabilty, Senior High school (SMA) students. Masa remaja adalah masa individu berada pada periode yang penting, periode peralihan, periode perubahan, masa mencari identitas, usia yang menimbulkan ketakutan, masa yang tidak realistik, dan sebagai ambang masa dewasa. Berdasarkan pernyataan Gesel,et.al, dapat dikatakan remaja usia 14 tahun tidak memiliki stabilitas emosi sehingga mudah untuk fluktuatif atau berubah-ubah emosinya. Remaja usia 16 tahun lebih memiliki stabilitas emosi sehingga memiliki kontrol emosional yang lebih baik. Fenomena di Indonesia, remaja yang berusia 16 tahun masih memiliki emosi yang mudah meledak dan sulit untuk mengendalikan perasaannya. Tujuan umum penelitian ialah merumuskan program hipotetik bimbingan dan konseling pribadi untuk meningkatkan stabilitas emosi peserta didik kelas XI SMA Angkasa Lanud Husein Sastranegara Bandung tahun ajaran 2012/2013. Adapun tujuan khusus yang ingin dicapai dalam penelitian ialah memperoleh gambaran profil stabilitas emosi peserta didik kelas XI SMA Angkasa Lanud Husein Sastranegara Bandung tahun ajaran 2012/2013. Metode yang digunakan dalam penelitian yaitu penelitian deskriptif untuk mendeskripsikan stabilitas emosi peserta didik kelas XI SMA Angkasa Lanud Husein Sastranegara Bandung tahun ajaran 2012/2013 serta upaya perumusan program hipotetik bimbingan dan konseling pribadi untuk meningkatkan stabilitas emosi pada peserta didik. populasi penelitian adalah seluruh peserta didik kelas XI SMA Angkasa Lanud Husein Sastranegara Bandung Tahun Ajaran 2012/2013, teknik pengambilan sampel penelitian dilakukan dengan menggunakan teknik simple random sampling yakni sebanyak 174 peserta didik. pada penelitian teknik pengumpulan data menggunakan teknik non-tes berupa angket yang mengungkap stabilitas emosi peserta didik. Hasil penelitian yang diperoleh yaitu: (1) tingkat stabilitas emosi peserta didik secara umum berada pada kategori tinggi di semua aspek kecuali pada aspek kemampuan menyelesaikan masalah berada pada kategori sedang. (2) rumusan program hipotetik bimbingan dan konseling sosial yang dinyatakan layak oleh pakar dan praktisi meliputi: rasional, perumusan visi dan misi, dasar dan landasan operasional, deskripsi kebutuhan, tujuan program, komponen program, personel yang dilibatkan, rencana operasional, pengembangan tema, pengembangan satuan layanan, waktu pelaksanaan, sarana dan prasarana, dan evaluasi. Rekomendasi ditujukan pada guru BK dapat menjadikan program bimbingan dan konseling pribadi untuk meningkatkan stabilitas emosi pada peserta didik kelas XI Tahun Ajaran 2012/2013 yang dirancang oleh peneliti sebagai pedoman pelaksanaan layanan bimbingan dan konseling pribadi untuk meningkatkan stabilitas emosi peserta didik. Rekomendasi bagi peneliti selanjutnya dapat membandingkan gambaran umum stabilitas emosi pada remaja awal dan remaja akhir, sehingga gambaran yang dihasilkan dapat lebih luas dan menyeluruh. Kata Kunci: Program Hipotetik Bimbingan dan Konseling Pribadi, Stabilitas Emosi, Peserta Didik SMA